THU0518 Dicam Attenuates Macrophage Differentiation via Suppression of Integrin αVβ3-Dependent Akt-Foxo3a-Irf7 Pathway. (10th June 2014) - Han, S.-W.; Jung, Y.-K.; Han, M.-S.; Lee, E.-J.; Park, H.-R.; Kim, G.-W.; Bae, G.-B.
Abstract : Background: DICAM, a dual Ig domain containing adhesion molecule, is involved in cell-cell adhesion through a direct interaction with αVβ3 integrin. In our previous study showing the inhibitory role in osteoclastogenesis, we found a clue that DICAM also has a suppressive role in macrophage differentiation. However, it remains still obscure the role of DICAM in macrophage differentiation and M1/M2 polarization. Objectives: To investigate the role of DICAM in macrophage differentiation and M1/M2 polarization. Methods: To induce differentiation into resting M0 macrophage, THP-1 cells were cultured with 100 nM PMA for 24 h, then rested for 6 days. For M1/M2 polarization, resting M0 THP-1 macrophages were treated with IFN-γ or IL-4 for 24 h. To investigate the role of DICAM during THP-1 macrophage differentiation, THP-1 cells were infected with 50 moi of control LacZ adenovirus or with DICAM adenovirus. Results: The expression of DICAM was increased during PMA-induced THP-1 differentiation, and DICAM was slightly decreased by IFN-γ for M1 polarization and increased by IL-4 for M2 polarization. The overexpresion of DICAM in THP-1 cells suppressed PMA-mediated macrophage differentiation in the number of activated branched macrophage and macrophage marker expression, CD14 and CD68. However, DICAM does not affect the viability and proliferation of PMA-stimulated THP-1 macrophage. Functionally, DICAM attenuated the TNF-α secretion of differentiated THP-1 cells and their phagocytic activity as well. To investigate the molecular mechanisms for DICAM-mediated suppression of macrophage differentiation, we conducted microarray analyses, which revealed that DICAM overexpression significantly suppressed type 1 interferon system. Among interferon regulatory factors (IRFs) family, IRF7 was most significantly reduced by DICAM. DICAM also attenuated Akt activation and increased a nuclear translocation of FoxO3a that is known to be a critical negative regulator of IRF7. Consistently, DICAM also decreased total integrin β3 level and integrin-linked kinase (ILK) phosphorylation, the major adaptor molecule of integrin β3. Based on the fact that type 1 interferon is important in M1 macrophage polarization, we investigated the role of DICAM in M1/M2 polarization of macrophage. Overexpression of DICAM induced downregulation of M1-associated genes such as IL-12b p40, IL12 p19, TNFa, IL-6, and IL-1b but did not affect M2 genes, Arg1 and Fizz1. In addition, DICAM increased IL-10, but decreased TNFa and INF-β. Conclusions: DICAM potently reduces differentiation and function of THP-1 macrophage and skews a THP-1 polarization into M2-like macrophage via suppression of integrin αVβ3-dependent Akt-FoxO3a-IRF7 pathway. References: Han SW, Jung YK, Lee EJ, Park HR, Kim GW, Jeong JH, et al. DICAM inhibits angiogenesis via suppression of AKT and p38 MAP kinase signalling. Cardiovasc Res 2013;98(1):73-82. Jung YK, Han SW, Kim GW, Jeong JH, Kim HJ, Choi JY. DICAM inhibits osteoclast differentiation through attenuation of the integrin alphaVbeta3 pathway. J Bone Miner Res 2012;27(9):2024-34. Jung YK, Jin JS, Jeong JH, Kim HN, Park NR, Choi JY. DICAM, a novel dual immunoglobulin domain containing cell adhesion molecule interacts with alphavbeta3 integrin. J Cell Physiol 2008;216(3):603-14. Acknowledgements: This work was supported by the National Research Foundation of Korea (NRF) grants funded by the Korea government (2011-0007402, 2013-R1A2A2A01069204). Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1478